Prediction of Surface Uplift in Post-Mining Areas Using Satellite Interferometry and Numerical Modelling – A Case Study - Vuong Nguyen, Phu Minh; Apanowicz, Bartosz; Walentek, Andrzej; Chen, Shoukai; Liu , Jinping (Archives of Mining Sciences, 2026)
In most coal mines across Europe, mining operations have already ceased, and the previously exploited geological strata have become partially or fully flooded. The process of mine flooding is gradual, often spanning several years or even decades. During this time, the water table within the re-saturating rock mass slowly rises toward the surface. As groundwater infiltrates and saturates the rock, it induces geomechanical changes, including the movement of rock blocks within the geological strata and the redistribution of local gravitational stresses. These changes result in stress accumulation and alterations in the geodynamic equilibrium of the region. Ultimately, such processes can lead to large-scale ground movements, including land subsidence, uplift, or the sudden formation of sinkholes in near-surface areas. Understanding and monitoring these phenomena are critical for mitigating geohazards associated with post-mining environments and ensuring the long-term stability of former mining regions. To support this goal, a study was conducted to predict surface uplift at the flooded Kazimierz-Juliusz coal mine in Poland using numerical modelling with FLAC2D, a finite difference method-based software. Based on extensive Satellite Radar Interferometry (InSAR) monitoring data, a numerical model was developed and subsequently verified for predictive analysis. Occurrence of surface uplift has been observed at the studied site, with a maximum displacement of approximately 16 cm at the end of 2023. Long-term predictions indicate that surface uplift could reach up to 57 cm when the water level rises to ground level. This research is expected to provide a valuable reference for understanding uplift phenomena and to contribute to a deeper insight into water-mechanical interactions within the rock mass in regions affected by mine flooding.